Women and paranaense painting: the relationship between art and gender (end of the nineteenth century and early twentieth century) - Priori, Claudia (História: Questões e Debates, 2017)
This article discusses the presence and women acting in the field of art paranaense in the late nineteenth century and early twentieth century, analyzing the spaces occupied by them in this art scene, their trajectories, expressions and also how these artists were seen and represented by society. For this, we conduct research in bibliographic production that deals with the theme, including magazines and newspapers of the time, as well as data collection by the collection of museums. Our part of the prospective approach of gender studies, in conjunction with the Art area, as this issue is still in need of attention from the history, reasons that encourage us to question the places of women in art, especially in painting, since the areas of education, art and culture were restricted and undeveloped in the newly emancipated province. Moreover, the world of arts and science was little occupied by women due to social constraints, roles and places to be occupied by females. Therefore, we analyze the relationship between art and gender, realizing the implications and difficulties in integrating women in the artistic field.